Digital Literacy and Digital Ethics Strengthening Program For Generation Z in The Information Era for High School Students - Masni Masni; Asrianti Asrianti; Andika Wahyudi Gani; Muhtar Muhtar; Irwansyah Suwahyu; Muhammad Asriadi (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
This community engagement program aims to enhance digital literacy and digital ethics among Generation Z, particularly high school students in grades XI and XII in Wonomulyo, in response to the complex challenges of the information era. As digital naives, Generation Z has broad access to technology but often lacks the critical and ethical skills necessary for responsible digital media use. This program was designed to provide a comprehensive understanding of how to use digital platforms wisely, safely, and ethically through participatory and experiential learning methods. The implementation included socialization sessions, interactive workshops, case simulations, group discussions, and student-led digital campaigns. The results showed a significant improvement in students’ conceptual understanding, critical thinking abilities, and ethical awareness in navigating digital content. Participants also displayed strong enthusiasm in formulating a digital code of ethics and raising collective awareness about the dangers of misinformation, cyberbullying, and negative digital footprints. With active support from school officials and facilitators, the program effectively fostered responsible digital citizenship. It is hoped that this initiative can be sustainably replicated within the school environment and further developed as part of a character education curriculum rooted in digital competence. Strengthening digital literacy and ethics is a crucial step in preparing young generations to face global challenges wisely and ethically.